PRAGMATICS ANALYSIS OF OMOTENASHI SPEECH ACTS USED BY FRONT OFFICE STAFF AT A STAR-RATED HOTEL IN SANUR - Ni Putu Sri Utami Putri; Eka Anastasia Wijaya (Lingua Scientia, 2026)
Front office staffs play a crucial role in creating a first impression for guests. The use of formal Japanese, or Keigo, serves as a vital pragmatic tool. Therefore, this study is important to be conducted for analysing how politeness strategies are implemented by front office staffs to bridge the gap between hotel protocols formality and personal warmth. This study employs a qualitative method to investigate the application of Omotenashi speech acts among front office staff at a star-rated hotel in Sanur. From the 20 utterances, 7 utterances act as directive function, 1 utterance act as commissive function, 4 utterances act as expressive and directive functions, 3 utterances act as assertive/informative function, 2 utterances act as expressive function, 1 utterance act as assertive function, and 2 utterances act as expressive and assertive functions. Further, 10 utterances contained elements of omotenashi furumai, 6 utterances contained elements of omotenashi shitsurai, and 4 utterances contained elements of omotenashi shikake. This study indicates that interactions at front desk mainly utilize directive speech acts (such as requesting information, directing visitors, and providing instructions) and expressive speech acts (such as greeting and expressing gratitude). Further, Furumai element (behaviour and etiquette) appeared most frequently in the data among the three elements of Omotenashi.